THE EFFECT OF TOBACCO SMOKING ON THE HUMAN BODY (Academicia Globe: Inderscience Research, 2023)
The article considers the influence of cigarette smoking on the state of the functional systems of the human body. The research data of a number of scientists on this issue is also presented.